Modeling soil erosion between 1985 and 2014 in three watersheds on the carbonate-rock dominated Guizhou Plateau, SW China, using WaTEM/SEDEM. (February 2021) - Luo, Yao; Wang, Hongya; Meersmans, Jeroen; Green, Sophie M.; Quine, Timothy A.; Feng, Siwen
The Guizhou Plateau, SW China is largely underlain by carbonate rocks. Because soils are thin, soil loss remains a serious problem despite low erosion rates. Further understanding the impacts of changes in rainfall, land use and differences in topography on sediment yield and delivery may assist in the development of suitable policies to reduce soil erosion on the plateau. A spatially distributed soil erosion and sediment delivery model (WaTEM/SEDEM) was applied to investigate temporal–spatial changes in soil erosion between 1985 and 2014 in three watersheds (Dadukou (DDK), Caopingtou (CPT) and Gaoche (GC)) located in the southwest Guizhou Plateau. The WaTEM/SEDEM model was calibrated and validated using data on sediment yields measured at the watershed scale. The total sediment yield (SY) and soil erosion modulus (SEM) firstly decreased followed by an increase, whereas the sediment delivery ratio (SDR) remained almost unchanged over the 30-year period. The major sediment source was dry farmlands. SY was the highest in the largest DDK watershed. The highest SEM occurred in the CPT watershed due to steep terrain and high ratio of dry farmland areas on steeper slopes. SEM was the lowest in the GC watershed where slope gradient and ratio of dry farmland on steeper slopes are low. SDR was the highest in the GC watershed because of its topographic characteristics. SEM was sensitive to precipitation fluctuations in the GC, DDK and particularly in the steep and intensively eroded CPT watershed, while changes in dry farmland ratio influenced the SEM in the CPT and DDK watersheds but not in the gentle and mildly eroded GC watershed. Changes in forest ratio had significant impacts on SEM only in the GC watershed. Since responses of soil erosion to variations or differences in the main impact factors differ in the different watersheds, soil conservation strategies should be watershed specific.